A best–worst scaling experiment to prioritize concern about ethical issues in citizen science reveals heterogeneity on people-level v. data-level issues - Christi J. Guerrini (Nature Portfolio, 2021)
Abstract “Citizen science” refers to the participation of lay individuals in scientific studies and other activities having scientific objectives. Citizen science gives rise to unique ethical issues that stem from the potentially multifaceted contributions of citizen scientists to the research process. We sought to explore the ethical issues that are most concerning to citizen scientist practitioners, participants, and scholars to support ethical practices in citizen science. We developed a best–worst scaling experiment using a balanced incomplete block design and fielded it with respondents recruited through the U.S.-based Citizen Science Association. Respondents were shown repeated subsets of 11 ethical issues and identified the most and least concerning issues in each subset. Latent class analysis revealed two respondent classes. The “Power to the People” class was most concerned about power imbalance between project leaders and participants, exploitation of participants, and lack of diverse participation. The “Show Me the Data” class was most concerned about the quality of data generated by citizen science projects and failure of projects to share data and other research outputs.